Psychopathology and resident status – comparing asylum seekers, refugees, illegal migrants, labor migrants, and residents - Heeren, Martina; Wittmann, Lutz; Ehlert, Ulrike; Schnyder, Ulrich; Maier, Thomas; Müller, Julia (Comprehensive psychiatry, 2014)
This study aimed to describe, compare, and predict mental health outcomes of different migrant groups and native residents in Switzerland. Asylum seekers (n=65); refugees holding permanent protection visas (n=34); illegal migrants (n=21); labor migrants (n=26); and residents (n=56) completed an assessment by questionnaire. Main outcome variables were symptoms of posttraumatic stress, anxiety and depression. It was tested whether resident status predicted psychopathology over and above the influence of control variables including social desirability, traumatic event types and post-migration resources. Asylum seekers (54.0%) and refugees (41.4%) fulfilled criteria of PTSD most frequently. Clinically relevant symptoms of anxiety and depression were most frequently reported by asylum seekers (84.6% and 63.1%, resp.) and illegal migrants (both 47.6%). Resident status contributed to psychopathology over and above the influence of control variables. Overall, asylum seekers, refugees, and illegal migrants showed high psychiatric morbidity. Differences in resident status appear to be specifically associated with mental health outcomes. This association persists even when controlling for social desirability, post-migration resources and traumatic events. This emphasizes the importance of current socio-political living conditions for mental health, even with respect to the psychopathological sequelae of past traumatic experiences.